2022
DOI: 10.1186/s12951-022-01405-w
|View full text |Cite
|
Sign up to set email alerts
|

Metal ions/nucleotide coordinated nanoparticles comprehensively suppress tumor by synergizing ferroptosis with energy metabolism interference

Abstract: Background Ferroptosis holds promise as a potential tumor therapy by programming cell death with a hallmark of reactive oxygen species (ROS)-induced lipid peroxidation. However, vigorous energy metabolism may assist tumors to resist oxidative damage and thus weaken the effects of ferroptosis in tumor treatment. Results Herein, a bifunctional antitumor platform was constructed via coordinated interactions between metal ions and nucleotides to synerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…The reduction in GAPDH expression was prevented by the ferroptosis inhibitor ferrostatin-1. Additionally, GAPDH knockdown boosted Fe 2+ -induced ferroptosis within tumor cells [ 21 ]. These results imply that ferroptosis affects glycolysis levels in lung cancer cells and that GAPDH may serve as a prognostic sign for lung cancer patients as well as a marker of ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in GAPDH expression was prevented by the ferroptosis inhibitor ferrostatin-1. Additionally, GAPDH knockdown boosted Fe 2+ -induced ferroptosis within tumor cells [ 21 ]. These results imply that ferroptosis affects glycolysis levels in lung cancer cells and that GAPDH may serve as a prognostic sign for lung cancer patients as well as a marker of ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the overexpression of GAPDH, but not of the other glycolytic enzymes studied, promoted tumor cell survival and resistance to chemotherapy in caspase-independent cell death by preserving a small number of intact mitochondria [ 20 ]. Reduced GAPDH expression in tumors slows the glycolytic pathway, interfering with the energy metabolism of the tumor and enhancing the death of tumor cells caused by ferroptosis [ 21 ]. However, further research is still needed to investigate the direct relationship between GAPDH and ferroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…By its very nature, the metalloenzyme is essentially just a type of functionalized nanomaterial with a metal architecture as an active center, stabilized by amino acids or nucleotides due to the natural selection and evolution. Even limited experiments have already demonstrated that nucleotides or amino acids can significantly improve or generate enzyme-like properties in an inorganic nanomaterial based on its architecture, 136,[265][266][267][268][269][270][271][272][273] providing further evidences that enzymes might have emerged from such evolutionary paths or why biocatalysts need further evolution. In other words, active metal sites in tertiary structures were selected first for their catalytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Triggered by visible blue light instead of UV light, the photoresponsive system generates Fe 2+ and ROS and inhibits GPX4, which leads to apoptosis- and ferroptosis-dependent cancer cell proliferation inhibition [ 111 ]. TAM polarization from the tumor-promoting M2 type to the tumor-killing M1 type is simultaneously activated by PEG-Fns, which concomitantly inhibits tumor growth and prevents pulmonary metastasis in vivo [ 112 ].
Fig.
…”
Section: Several Breakthroughs Of Nanometallic Materials In Cancer Im...mentioning
confidence: 99%